2015
DOI: 10.1007/s11356-015-4401-2
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate esters contamination in soils and vegetables of plastic film greenhouses of suburb Nanjing, China and the potential human health risk

Abstract: The contamination of phthalate esters (PAEs) has become a potential threat to the environment and human health because they could be easily released as plasticizers from the daily supply products, especially in polyethylene films. Concentration levels of total six PAEs, nominated as priority pollutants by the US Environmental Protection Agency (USEPA), were investigated in soils and vegetables from four greenhouse areas in suburbs of Nanjing, East China. Total PAEs concentration ranged from 930±840 to 2 450±71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…The result in this study was in good agreement with that in the study conducted by Ma et al (2003), in which the PAE concentrations in greenhouse soils from the outskirts of Beijing were determined and the concentrations of DEHP were also lower than that of DnBP. However, it was reported that the concentrations of DEHP were higher than those of DnBP in greenhouse vegetable soils in Nanjing, South, China Ma et al, 2015). This variation may be caused by difference in the manage modes and climate condition between northern and southern regions of China.…”
Section: Occurrence and Distribution Of Paes In Soilsmentioning
confidence: 96%
“…The result in this study was in good agreement with that in the study conducted by Ma et al (2003), in which the PAE concentrations in greenhouse soils from the outskirts of Beijing were determined and the concentrations of DEHP were also lower than that of DnBP. However, it was reported that the concentrations of DEHP were higher than those of DnBP in greenhouse vegetable soils in Nanjing, South, China Ma et al, 2015). This variation may be caused by difference in the manage modes and climate condition between northern and southern regions of China.…”
Section: Occurrence and Distribution Of Paes In Soilsmentioning
confidence: 96%
“…Since they are not covalently bound to plastics, phthalates can be released into the environment and have been widely detected in China [e.g., air (Wang et al, 2016), soils (Ma et al, 2015), drinking water and edible food commodities (Ji et al, 2014)]. Humans may be exposed to these chemicals via ingestion, inhalation, and dermal absorption (Wittassek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Phthalates, which are primarily used as plasticizers to induce the flexibility and workability of polymeric materials, are another group of environmental pollutants that possess endocrine-disrupting properties (Gray et al, 2000;Howdeshell et al, 2008). High concentrations of phthalates have been detected in the drinking water (Li et al, 2010), as well as in the soils and vegetables in agricultural areas of China (Ma et al, 2015). Humans are constantly exposed to phthalates through ingestion, inhalation and dermal absorption.…”
Section: Introductionmentioning
confidence: 99%